Strategi Pengembangan Kurikulum Pendidikan Agama Islam Multikultural Di SMA Islam Sabilunnajah - Muhammad Zainal Arifin; Sri Wahyuni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Low insight and understanding of religion is one of the causes of ethnic and religious-based conflicts, so it must be addressed as a serious matter.​​​​ From this, Islamic education is very important to be implemented in a multicultural environment so that the needs of diverse communities can be met.​​​​ The type used in this research is a case study with a qualitative approach, and it was implemented. Data collection techniques were direct observation at Sabilunnajah Islamic High School, the sources interviewed in this research were the principal and PAI teachers, document analysis was also used reinforcement in this research.​​ The data obtained was analyzed, researched, and interpreted in a qualitative descriptive manner.​​ The results obtained were that the formulation of the PAI curriculum that was applied was flexible based on an analysis of the situation of the general public. The PAI design adopted aims to increase multicultural awareness in society by considering the conditions of students and educators who carry out educational activities. The strategy used is to introduce multicultural values ​​such as forgiveness and respect. , the national spirit, emphasizes the importance of good relations between teachers, educational institutions and between the general publ